Microbiology fundamentals : a clinical approach - Cowan, Marjorie Kelly; Smith, Heidi (New York, NY : McGraw Hill Education, 2022)
Cowan's Microbiology Fundamentals: A Clinical Approaches a perfect fit for your microbiology course. The author team includes a practicing Registered Nurse who shows students how the content on each page relates to their lives and future career. McGraw Hill Connect is aligned with the text and provides a highly reliable, easy-to-use homework and learning management solution that embeds learning science and award-winning adaptive tools to improve student results.
1 Introduction to Microbes and Their Building Blocks -- 2 Tools of the Laboratory: Methods for the Culturing and Microscopic Analysis of Microorganisms -- 3 Bacteria and Archaea -- 4 Eukaryotic Cells and Microorganisms -- 5 Viruses and Prions -- 6 Microbial Nutrition and Growth -- 7 Microbial Metabolism -- 8 Microbial Genetics and Genetic Engineering -- 9 Physical and Chemical Control of Microbes -- 10 Antimicrobial Treatment -- 11 Interactions Between Microbes and Humans -- 12 Host Defenses I: Overview and Innate Defenses -- 13 Host Defenses II: Adaptive Immunity and Immunization -- 14 Disorders in Immunity -- 15 Diagnosing Infections -- 16 Infectious Diseases Affecting the Skin and Eyes -- 17 Infectious Diseases Affecting the Nervous System -- 18 Infectious Diseases Affecting the Cardiovascular and Lymphatic Systems -- 19 Infectious Diseases Affecting the Respiratory Systems -- 20 Infectious Diseases Affecting the Gastrointestinal Tract -- 21 Infectious Diseases Affecting the Genitourinary System -- 22 One Health: The Interconnected Health of the Environment, Humans, and Other Animals.
Includes index.
Keywords: MICROBIOLOGY